The Ideal Masculinity of Male Ninjas in Naruto and Naruto Shippuden Anime Series - Jennisa Mayang Deviani; Jenny Mochtar (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Shounen is one of the most popular genres of anime. Although Shounen is usually targeted at younger boys, it is often consumed by audiences of all ages, such as Naruto and its sequel, Naruto Shippuden. In this study, I will focus on identifying the masculinity within the male ninjas in the series and analyzing the motivations behind the exercise of masculinity to find the ideal masculinity. I will combine the masculinity theory with the Japanese’s manhood, to analyze the ideal masculinity in the text. Through my analysis, I find that the male ninjas of these anime series show different kinds of masculinity, which divides them into two roles, protagonist and antagonist. The protagonists are the ones who thrive to fight for others while the antagonists fight only to benefit themselves. As a result, the protagonists are able to possess the ideal masculinity as they can exercise their masculinity positively.Keywords: anime, masculinity, male ninjas, protagonist, antagonist.